Comparison of ground sections, paraffin sections and micro-CT imaging of bone from the epiphysis of the porcine femur for morphometric evaluation - Kubíková, Tereza; Bartoš, Martin; Juhas, Štefan; Suchý, Tomáš; Sauerová, Pavla; Hubálek-Kalbáčová, Marie; Tonar, Zbyněk (Annals of anatomy, 2018)
The aim of this study was to compare data on the volume fraction of bone and the thickness of the cortical compact bone acquired during microcomputed tomography (micro-CT) analysis with data acquired from identical samples using stereological analysis of either decalcified paraffin sections or ground sections. Additionally, we aimed to compare adjacent tissue samples taken from the major trochanter of the porcine femur to map the basic biological variability of trabecular bone. Fifteen pairs of adjacent tissue blocks were removed from the major trochanter of the proximal epiphyses of porcine femurs (female pigs aged 24-39 months, weight=59.16±8.15kg). In each sample, the volume of the cortical compact bone, the volume of the trabecular bone, and the thickness of the cortical compact bone was assessed using micro-CT. Afterwards, half of the samples were decalcified and processed using paraffin histological sections. Another half was processed into ground sections. The volume and thickness of bone was assessed in histological sections using stereological techniques. There were no significant differences in the bone volumes and thicknesses measured by micro-CT and the corresponding values quantified in decalcified sections. Similarly, there were no differences between the results from micro-CT and the analysis of the corresponding ground sections. Histomorphometric studies based on relatively low numbers of undecalcified ground sections or demineralized paraffin sections of bone yield data on bone volume and the thickness of cortical compact bone that is comparable with three-dimensional micro-CT examination. The pilot data on the variability of cortical compact bone and trabecular bone volumes in the porcine major trochanter provided in this study aim for planning experiments in the field of bone healing and implantology.
Keywords: Femur; rentgenová mikrotomografie; Paraffin Embedding; Bone and Bones; Pig; dekalcifikace (technika); Sus scrofa; anatomie průřezová; Swine; kosti a kostní tkáň; ženské pohlaví; Bone volume; zvířata; Tissue Fixation; Decalcification Technique; Histomorphometry; fixace tkání; Stereology; prasata; femur; zalévání tkání do parafínu; Cortical compact bone; Trabecular bone; Female; Anatomy, Cross-Sectional; X-Ray Microtomography; Animals